Evaluation of the food, nutrition value, and alpha-glucosidase inhibitory activity of the ripe and unripe fruit of Rubus steudneri Schweinf - Raghavendra, H. L. [UNESP]; Kekuda, T. R. Prashith; Upashe, S. P.; Dsilva, F.; Ravikumar Patil, H. S.; Shivanandappa, K. C. (Univ Putra Malaysia Press, 2022)
Rubus steudneri Schweinf. (Rosaceae) is one of the three unstudied Rubus species that grow in Ethiopia. The present work was aimed to determine the physicochemical characteristics, micronutrients, anthocyanins, and antinutrients of ripe and unripe R. steudneri fruits using a range of analytical protocols. The present work also investigated the alpha-glucosidase inhibitory activity of ripe and unripe fruits. The total and acid-insoluble ash contents of ripe fruits were higher than those of unripe fruits. Changes in the micronutrient contents and antinutrients were also observed during ripening. Ripe fruits contained anthocyanins, mineral elements, and water-soluble vitamins, namely niacin and pyridoxine, in higher quantities than in unripe fruits. Toxic heavy metals were not detected in both ripe and unripe fruits. There were lower amounts of tannin and phytic acid in ripe fruits than in unripe fruits. Both ripe and unripe fruit extracts displayed inhibitory activity against alpha-glucosidase. Greater inhibitory activity was shown by ripe fruits than unripe fruits, as indicated by the IC50 values. The total phenolics and flavonoids were slightly higher in unripe fruits. The lower contents of antinutrients (tannin and phytic acid), and the absence of toxic heavy metals indicate the edibility of R. steudneri fruits. The ripe and unripe fruits can also be used to manage diabetes mellitus as the extracts displayed inhibitory potential against alpha-glucosidase. The observed inhibitory activity could be ascribed to the phenolics and flavonoids of the fruits. (c) All Rights Reserved
Keywords: Rubus steudneri; Anthocyanins; Phytic acid; Tannin; Flavonoid; Diabetes mellitus